A Quantitative Method for the Evaluation of Deep Vein Thrombosis in a Murine Model Using Three-Dimensional Ultrasound Imaging - Yanjun Xie; Yi Huang; Hugo C. S. Stevenson; Li Yin; Kaijie Zhang; Zain Husain Islam; William Aaron Marcum; Campbell Johnston; Nicholas Hoyt; Eric William Kent; Bowen Wang; John A. Hossack (Biomedicines, 2024)
Deep vein thrombosis (DVT) is a life-threatening condition that can lead to its sequelae pulmonary embolism (PE) or post-thrombotic syndrome (PTS). Murine models of DVT are frequently used in early-stage disease research and to assess potential therapies. This creates the need for the reliable and easy quantification of blood clots. In this paper, we present a novel high-frequency 3D ultrasound approach for the quantitative evaluation of the volume of DVT in an in vitro model and an in vivo murine model. The proposed method involves the use of a high-resolution ultrasound acquisition system and semiautomatic segmentation of the clot. The measured 3D volume of blood clots was validated to be correlated with in vitro blood clot weights with an R<semantics>2</semantics> of 0.89. Additionally, the method was confirmed with an R<semantics>2</semantics> of 0.91 in the in vivo mouse model with a cylindrical volume from macroscopic measurement. We anticipate that the proposed method will be useful in pharmacological or therapeutic studies in murine models of DVT.